CONTROLS ON STABLE SULFUR ISOTOPE FRACTIONATION DURING BACTERIAL SULFATE REDUCTION IN ARCTIC SEDIMENTS - Bruchert V.; Knoblauch C.; Jorgensen B.B. (My University, 2001)
Sulfur isotope fractionation experiments during bacterial sulfate reduction were performed with recently isolated strains of cold-adapted sulfate-reducing bacteria from Arctic marine sediments with year-round temperatures below 2°C. The bacteria represent quantitatively important members of a high-latitude anaerobic microbial community. In the experiments, cell-specific sulfate reduction rates decreased with decreasing temperature and were only slightly higher than the inferred cell-specific sulfate reduction rates in their natural habitat. The experimentally determined isotopic fractionations varied by less than 5.8%% with respect to temperature and sulfate reduction rate, whereas the difference in sulfur isotopic fractionation between bacteria with different carbon oxidation pathways was as large as 17.4%%. Incubation of sediment slurries from two Arctic localities across an experimental temperature gradient from -4°C to 39°C yielded an isotopic fractionation of 30%% below 7.6°C, a fractionation of 14%% and 15.5%% between 7.6°C and 25°C, and fractionations of 5%% and 8%% above 25°C, respectively. In absence of significant differences in sulfate reduction rates in the high and low temperature range, respectively, we infer that different genera of sulfate-reducing bacteria dominate the sulfate-reducing bacterial community at different temperatures. In the Arctic sediments where these bacteria are abundant the isotopic differences between dissolved sulfate, pyrite, and acid-volatile sulfide are at least twice as large as the experimentally determined isotopic fractionations. On the basis of bacterial abundance and cell-specific sulfate reduction rates, these greater isotopic differences cannot be accounted for by significantly lower in situ bacterial sulfate reduction rates. Therefore, the remaining isotopic difference between sulfate and sulfide must derive from additional isotope effects that exist in the oxidative part of the sedimentary sulfur cycle.